Physical and Mechanical Properties: Effect of Substitution of EFB Filler on the Processing of Lump-Based Motorcycle Foot Pad Compounds - Supriyanto Supriyanto; Giffary Pramafisi Soeherman; Pridata Gina Putri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Lump is one of the processed rubber materials derived from latex of rubber trees and clusters of latex obtained from the Hevea Brasiliensis tree. Generally, lumps can be utilized as the basic material for component manufacturing. In the production of component products, additives such as filling materials, vulcanization agents, plasticizers, activators, antioxidants, and accelerators are required. This research utilizes EFB charcoal as a filling material in the production of rubber components to substitute carbon black, which will be used as a motorcycle footrest pad. The objective of this study is to analyze the characteristics of rubber components for motorcycle footrest pads with EFB filler as a filling material, and to obtain the best formulation in rubber component manufacturing that meets the hardness test parameters according to the Indonesian National Standard (SNI). The method used is a Completely Randomized Design (CRD) with one factor, namely the rubber component formula. This study consists of 5 treatments repeated 4 times, resulting in 20 experimental units. The results of the study showed that the physical and mechanical properties of each substitution treatment had the same characteristics with a reduction or decrease in test results for each test parameter carried out. However, based on the test results for each test parameter carried out, there were only 4 treatments that were still included in the SNI standard for hardness tests for step motors, namely F1 (0:60), F2(10:50), F3(20:40) and F4(30:30).. While the F5(40:20)treatment was still below the SNI standard. The best treatment was still obtained in the F2(10:50) treatment with a hardness value of 69.05 Shore A. Contribution to Sustainable Development Goals (SDGs):SDGs 8: Decent Work and Economic GrowthSDGs 9: Industry, Innovation and InfrastructureSDGs 12: Responsible Consumption and ProductionSDGs 13: Climate ActionSDGs 15: Life on Land